La inadecuada recolección y tratamiento de los desechos en el Cantón Quinsaloma y su incidencia en los derechos del Buen Vivir - Segura Contreras, Rolando Rigoberto (2016)
Rapid industrialization has led to countless polluting factors that have deteriorated terrestrial, atmospheric and aquatic resources with toxic materials, threatening and endangering the health of people and ecosystems. As the objective of this research project provide an overview of the possible causes of environmental pollution, especially that produced by emissions from solid waste for lack of control in the collection, they are affecting the city, especially children and elderly people. The increasingly widespread and intensive use of materials and energy has led to increasing pressure on the quality of local, regional and global ecosystems, which has made a concerted effort is undertaken to reduce the impact of pollution. It is therefore necessary that the GAD Quinsaloma make an amendment to the existing municipal ordinances so that the inhabitant aware of the need to keep the city clean and in keeping with the environment, not to cause chaos in the collection and treatment waste and environmental pollution, for which determine what are the main constitutional rights and guarantees. legally justify the harm to human health and the inhabitants of Quinsaloma Canton province of the Rivers.